2016
DOI: 10.2147/ppa.s109941
|View full text |Cite
|
Sign up to set email alerts
|

Time to lack of persistence with pharmacological treatment among patients with current depressive episodes: a natural study with 1-year follow-up

Abstract: IntroductionMedication nonadherence remains a big challenge for depressive patients. This study aims to assess and compare the medication persistence between unipolar depression (UD) and bipolar depression (BD).MethodsA total of 146 UD and 187 BD patients were recruited at their first index prescription. Time to lack of persistence with pharmacological treatment (defined as a gap of at least 60 days without taking any medication) was calculated, and clinical characteristics were collected. Final diagnosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…We are not aware of prior studies that have ever explored and compared such predictive model between UD and BD patients. Although our previous study found that predictors of premature dropout differed between UD and BD, 4 in the absence of replicating data, it is still premature to extensively speculate that such difference reflects different nature of these two diseases.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…We are not aware of prior studies that have ever explored and compared such predictive model between UD and BD patients. Although our previous study found that predictors of premature dropout differed between UD and BD, 4 in the absence of replicating data, it is still premature to extensively speculate that such difference reflects different nature of these two diseases.…”
Section: Discussionmentioning
confidence: 76%
“… 3 However, previous studies have shown that the rates of adherence to medication among patients with MDE are less than optimal. For instance, in our previous study, 4 more than 60% patients with MDE abandoned medication treatment within 12 months after treatment initiation, and over 40% gave up treatment in the first 3 months. Similar treatment discontinuation rates are also seen in other studies.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations